Ultrasound screening for thyroid nodules and cancer in individuals with family history of thyroid cancer: a micro-costing approach - Grani, G.; Lamartina, L.; Montesano, T.; Maranghi, M.; Filetti, S.; Durante, C.; Lopatriello, S. (Journal of endocrinological investigation, 2023)
Purpose Screening programs that target healthy populations are an important tool for identifying unrecognized, asymptomatic disease. However, ultrasound screening for thyroid cancer has no obvious advantage in terms of cost-effectiveness in asymptomatic adults. There is far less consensus (and data) on the indications for screening in high-risk individuals. The aim of the study was to estimate the costs of ultrasound screening for individuals with first-degree family history of thyroid cancer. Methods We conducted a prospective cross-sectional study from January 1, 2009 through December 31, 2018 in the Thyroid Cancer Outpatient Clinic of a large teaching hospital in Rome, Italy. We estimated the costs of an ultrasound screening protocol using the micro-costing bottom-up method. Results For individuals without thyroid nodules, the screening examination had an estimated cost of €66.21 per screenee. For those found to have unsuspicious nodules, the estimated cost rose to €119.52 per screenee, owing to the addition of thyroid function tests. The estimated cost of screening for a subject with newly diagnosed nodules that were submitted to cytology was €259.89. The total cost of screening for the entire population of 1176 individuals was € 118,133.85. The total expenditure to confirm a single thyroid cancer diagnosis was €10,598.71. Conclusion A sonographic screening implies a significant direct expenditure and is likely to detect a very large number of individuals with benign nodules (more than 45 asymptomatic individuals are diagnosed with a thyroid nodule for each newly detected cancer case), whose long-term follow-up will further increase healthcare costs.